MANAJEMEN PEMBELAJARAN FIQIH DI TK DARUL HIKMAH GARUT - Hanifah, Farah; Rahayu, Fitria (Al’ulum Jurnal Pendidikan Islam, 2024)
Fiqh learning is one of the learning that discusses the foundations of Islamic religious values. The existence of Fiqh learning at this early age level is a very good thing, this is because in the development of early childhood, the development can still be said to be very stable. This study aims to describe the delivery of Fiqh learning at Darul Hikmah Kindergarten Garut. This research was qualitative research conducted at Darul Hikmah Kindergarten Garut, West Java. The data collection technique used interviews with Islamic Education Teachers at Darul Hikmah Kindergarten Garut, observation and documentation. The results of this study indicate that the delivery of Fiqh learning at Darul Hikmah Kindergarten Garut is carried out through three stages, namely the planning, implementing and evaluating stages. At the planning stage, it is done by preparing a learning plan at the beginning of the semester. At the implementing stage, fiqh learning at Darul Hikmah Kindergarten is included in religious learning which is usually carried out once a week, precisely on Fridays by using the Merdeka Belajar curriculum. At the evaluation stage, it is carried out using checklists, anecdotal notes, or verbal exams.